2021
DOI: 10.1038/s41598-021-92661-7
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial neurovascular network (ANVN) to study the accuracy vs. efficiency trade-off in an energy dependent neural network

Abstract: Artificial feedforward neural networks perform a wide variety of classification and function approximation tasks with high accuracy. Unlike their artificial counterparts, biological neural networks require a supply of adequate energy delivered to single neurons by a network of cerebral microvessels. Since energy is a limited resource, a natural question is whether the cerebrovascular network is capable of ensuring maximum performance of the neural network while consuming minimum energy? Should the cerebrovascu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…This assumption forms the basis of interpreting functional neuroimaging techniques (Raichle, 2000(Raichle, , 2009Raichle & Mintun, 2006). However, recent years have shown that vascular feedback may influence neural signals in critical ways (Chander & Chakravarthy, 2012;Chhabria & Chakravarthy, 2016;Kim et al, 2016;Kumar, Mayakkannan, et al, 2021;Ranasinghe et al, 2015;Roy et al, 2021). Here, we modelled interactions between neurons and blood vessels, including a lateral connectivity network among vessels, to shed light on how vascular dynamics might generate tuned vascular responses and how these responses affect neuronal network structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption forms the basis of interpreting functional neuroimaging techniques (Raichle, 2000(Raichle, , 2009Raichle & Mintun, 2006). However, recent years have shown that vascular feedback may influence neural signals in critical ways (Chander & Chakravarthy, 2012;Chhabria & Chakravarthy, 2016;Kim et al, 2016;Kumar, Mayakkannan, et al, 2021;Ranasinghe et al, 2015;Roy et al, 2021). Here, we modelled interactions between neurons and blood vessels, including a lateral connectivity network among vessels, to shed light on how vascular dynamics might generate tuned vascular responses and how these responses affect neuronal network structures.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent experimental observations support the idea that cerebral microvessels can influence information coding in neurons (Kim et al, 2016; Roy et al, 2021). Additionally, computational models developed by our group suggest that information processing in the cerebral microvasculature may occur in tandem with neural information processing (Chander & Chakravarthy, 2012; Chhabria & Chakravarthy, 2016; Kumar, Khot, et al, 2021; Kumar, Mayakkannan, et al, 2021). Therefore, we included a feedback component from the vasculature to the neural layer and sought to determine if this could affect neuronal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of a healthy vasculature in shaping the function of the neural network has been discussed extensively ( Moore and Cao, 2008 ; Pradhan and Chakravarthy, 2011 ; Chander and Chakravarthy, 2012 ; Chhabria and Chakravarthy, 2016 ; Tourigny et al, 2019 ; Bright et al, 2020 ; Kumar et al, 2021a , b ). Neurodegenerative diseases are being traced back to an impaired neurovascular functional coupling ( Iadecola, 2004 , 2017 ; Shabir et al, 2018 ; Ahmad et al, 2020 ; Muddapu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of a healthy vasculature in shaping the function of the neural network has been discussed extensively [39][40][41][42][43][44][45][46]. Neurodegenerative diseases are being traced back to an impaired neurovascular functional coupling [1,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%